Analysis of Students' Errors in Solving Physics Problems Based on Bloom's Cognitive Levels - Sigit, Sigit; Gustina, Gustina (CV. Dharma Samakta Edukhatulistiwa, 2025)
This study aims to analyze students' errors in solving physics problems based on Bloom's cognitive levels, particularly at the application level (C3), focusing on the simple machines topic. Conducted at SMP Negeri 11 Palu with Grade VIII students, this qualitative descriptive research involved 20 participants, with six respondents selected through purposive sampling categorized as high, medium, and low achievers. Data were collected using essay tests and interviews, analyzed through error categorization (translation, conceptual, strategic, and computational errors). The findings reveal that translation errors were the most frequent (58.3%), followed by conceptual errors (41.6%), strategic errors (20.8%), and computational errors (16.6%). The study highlights students' difficulty in interpreting problem statements, applying correct formulas, and executing problem-solving steps accurately. These findings emphasize the importance of addressing students' conceptual understanding and problem-solving skills in physics education. Future studies should explore interventions to minimize these errors and enhance learning outcomes.